Targeting RNA N6-methyladenosine modification—— a novel therapeutic target for HER2- positive gastric cancer - Jia, Lijun; Zhang, Di; Zeng, Xiaoman; Wu, Li; Tian, Xiaowei; Xing, Na (Frontiers in Oncology, 2024)
Gastric cancer is one of the most common cancers and is considered the 5 th most frequent occurring cancer worldwide. It has gained great attention from the clinicians and researchers because of high mortality rate. It is generally treated with chemotherapy, radiotherapy, and surgery. Recently, additional treatment options including immunotherapy and targeted therapy and immunotherapy have been developed. However, poor prognosis, limited survival rate of patients, and drug resistance to treatment remain critical problems. To improve treatment options or to overcome the bottleneck of treatment, identification of diagnostic and prognostic markers, determining the most effective therapeutic options, and uncovering the molecular regulations associated with treatment strategies are required. In this regard n 6 -methyladenosine (m6A) regulation is considered important. This reversible modification plays a crucial role in progression, development and treatment of HER2-positive gastric cancer. Here, we discuss the role of m6A modification in HER2-positive gastric cancer progression through collecting related studies at present. We further discuss the association of m6A modification with therapeutic efficacy in HER2-positive gastric cancer and list some examples. We conclude that modification of m6A can be a new strategy for improving the prognosis and survival rate of HER2-positive gastric cancer patients.